Implementation of the WASPAS Method in Selection Librarian FST UIN Sumatera Utara - Suendri; Anggika Wardani (Jurnal Sistem Cerdas, 2024)
The selection of prospective librarians is necessary to make the right decisions and determine the most suitable individual to meet the library's needs. However, in facing the complexity of changes in the information environment and technological developments, the FST library often needs help selecting prospective librarians using manual calculations, which can affect the effectiveness of the library head and staff in selecting. This research was conducted at the FST Library of the North Sumatra State Islamic University. This time, the researchers used the Weighted Aggregated Sum Product Assessment (WASPAS) method to select prospective librarians. The criteria used are communication skills (C1), mastery of technology (C2), customer service (C3), limited skills (C4), and lack of adaptability (C5). Then, the alternatives used were five samples of prospective librarians who registered at the FST library. The calculations using the WASPAS method showed that the alternative Nazla Maulida (A04) was a suitable candidate to become a librarian at the FST library with a total score of 0.854.